1979
DOI: 10.1002/app.1979.070240307
|View full text |Cite
|
Sign up to set email alerts
|

Preferential wetting phenomenon in bicomponent polymer melt flow

Abstract: SynopsisFor two polymer melts spun in a side-by-side configuration through a capillary, interface shape and spinneret exit angle data are presented as a function of viscosity ratio, spinneret dimensions, and relative polymer-steel wettability. Nylon-nylon versus nylon-polyurethane bicomponent flow systems are compared. A surface tension phenomenon is postulated to be significant in controlling the bicomponent fiber interface shape for capillary length-to-diameter ratios of the order of unity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Figure 2 shows the relationship between the difference in the viscosity between the two phases and the TRDP configuration. [17][18][19][20] In fluid mechanics, viscous dissipation is manifested by the transformation of kinetic energy into thermal energy through fluidic viscosity. The viscous dissipation (E) per unit length in a two-phase flow of solvents a and b is expressed as follows.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the relationship between the difference in the viscosity between the two phases and the TRDP configuration. [17][18][19][20] In fluid mechanics, viscous dissipation is manifested by the transformation of kinetic energy into thermal energy through fluidic viscosity. The viscous dissipation (E) per unit length in a two-phase flow of solvents a and b is expressed as follows.…”
Section: Resultsmentioning
confidence: 99%
“…At a given melt temperature, viscosity ratio reversal can be obtained when the two components have viscosities such that crossovers occur in the plots of melt viscosity vs shear rate [1,2,4]. Experimental observations [1,2,5] have shown that interface curvature reversal occurred at approximately the shear rate where the viscosity crossover of the two melts also occurred.…”
Section: Effect Of Shearing Level Carreau-type Fluidsmentioning
confidence: 97%
“…However, it has been experimentally established that the viscosity difference between the two melts predominates over the elasticity ratio in determining the interface shape and the direction of encapsulation [1,5,4,8]. Based on this fact, this work focuses on the effect of the viscous properties on the interface deformation phenomena.…”
Section: Introductionmentioning
confidence: 97%
“…(12) and (13) with the momentum balance and energy balance equations, i.e., eqs. ( 6 ) and (7), numerical simulation of bicomponent spinning was carried out. In these equations, the mutual interaction between two components arising from a radial normal stress difference was neglected.…”
Section: Upper-convected Maxwell Modelmentioning
confidence: 99%